Asymmetry in serial femtosecond crystallography data. Issue 2 (30th January 2017) - Sharma, Amit; Johansson, Linda; Dunevall, Elin; Wahlgren, Weixiao Y.; Neutze, Richard; Katona, Gergely
Abstract : Distribution analysis of intensity observations in serial femtosecond crystallography data processing helps to separate Bragg reflections from the background detector response. Abstract : Serial crystallography is an increasingly important approach to protein crystallography that exploits both X‐ray free‐electron laser (XFEL) and synchrotron radiation. Serial crystallography recovers complete X‐ray diffraction data by processing and merging diffraction images from thousands of randomly oriented non‐uniform microcrystals, of which all observations are partial Bragg reflections. Random fluctuations in the XFEL pulse energy spectrum, variations in the size and shape of microcrystals, integrating over millions of weak partial observations and instabilities in the XFEL beam position lead to new types of experimental errors. The quality of Bragg intensity estimates deriving from serial crystallography is therefore contingent upon assumptions made while modeling these data. Here it is observed that serial femtosecond crystallography (SFX) Bragg reflections do not follow a unimodal Gaussian distribution and it is recommended that an idealized assumption of single Gaussian peak profiles be relaxed to incorporate apparent asymmetries when processing SFX data. The phenomenon is illustrated by re‐analyzing data collected from microcrystals of the Blastochloris viridis photosynthetic reaction center and comparing these intensity observations with conventional synchrotron data. The results show that skewness in the SFX observations captures the essence of the Wilson plot and an empirical treatment is suggested that can help to separate the diffraction Bragg intensity from the background.